The Effectiveness of Glucose and Honey Solution on the Duration of Second Stage of Labor in Primigravida - Nabilah Vista; Podojoyo Podojoyo; Eprila Eprila (Journal of Maternal and Child Health Sciences (JMCHS), 2021)
Background: According to WHO (2018) 8% of maternal deaths are caused by prolonged labor. The long duration of the second stage of labor is one of the factors that cause prolonged labor. For this reason, oral intake is recommended to meet the needs of the mother during labor. Giving glucose and honey as an oral alternative during labor was chosen because the time needed to become energy is relatively fast so that it can be given to mothers during labor and can provide oral intake for mothers in labor to accelerate the second stage and prevent prolonged labor. Purpose: To determine the effectiveness of giving glucose and honey solution on the duration of the second stage of labor in Midwife’s Independent Practice Methods: This research is a quantitative research using a quasi-experimental design research method. 30 respondents based on inclusion criteria were divided into two groups and intervened with a solution of glucose and honey. The duration of the second stage of labor was observed for each respondent and analyzed through the unpaired T-Test. Results: The results of the unpaired T statistic test obtained a p-value of 0.021 (p-value <0.05). There were differences in the duration of the second stage of labor in respondents who were given honey and glucose solution. The average duration of the second stage of labor in the treatment group that was given honey was 5.14 minutes shorter than the group given the glucose solution. Conclusion: There is a difference in the duration of the second stage of primigravida labor in pregnant women who are given honey and glucose solution. Giving honey is more effective in accelerating the duration of the second stage of labor in primigravida at PMB Palembang in 2021